Relationship between anxiety index and self-efficacy among counsellor trainees - Agnes Kong Yi, Jing (Universiti Malaysia Sarawak, (UNIMAS), 2018)
This research is aimed to investigate the anxiety index of the counsellor trainees and the relationship between anxiety index and self-efficacy among counsellor trainees. This proposed research utilized correlational research design. 150 counselor trainees recruited for data collection by using stratified random sampling. 2 instruments implemented in this study, which are State- Trait Anxiety Inventory (STAI) and generalized self-efficacy scale (GSE). STAI used to measure the anxiety index among counsellor trainees while GSE used to measure the scale of self-efficacy of counsellor trainees. The collected data analyzed by using Pearson Coefficient Correlation and independent samples t-test. Results revealed that there was significant relationship between anxiety index and self-efficacy. Besides that, there was no significant differences in anxiety index between gender of counsellor trainees. The results also showed that there are no significant differences in self-efficacy between male and female.